Study on the Adherence to the Code of Ethics of Select Customs Broker Practitioner in the Philippines - Doyo, Joan R.; Gutierrez, Ernell Bautista; Dante, Julian M.; Agapay, Arnel B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Every profession has a different focus of specialization and every professional’s competence are measured against their level of expertise, effectiveness, and efficiency. Meanwhile, conflict is inevitable, and it may cause destructive impacts if not managed properly. On one hand, Custom Brokers, as per “Custom, Broker Act of 2004” are professionals who render consultation, preparation of customs requisite document for imports and exports, declaration of taxes, etc. The study assessed the extent of adherence of customs brokers to code of ethics in terms of Competence, Respect, Integrity, Justice and Fairness. The customs broker’s adherence indicates the extent of practice of their code of ethics and results revealed that, customs brokers usually and always adhere to code of ethics. However, results also revealed that, there is a significant difference in the assessment of the Customs Broker Practitioners towards adherence to Code of Ethics.